Nitrogen chemistry of hycean worlds on the example of K2-18b - Radecka, Maja W; Rimmer, Paul B (Oxford University Press (OUP), 2025)
Abstract A recent observation of the exoplanet K2-18b sparked interest among scientists - large amounts of carbon dioxide and methane were detected in an H2-rich background atmosphere. If the planet is a hycean world (liquid water ocean + hydrogen-dominated atmosphere), it could be habitable under certain conditions. The presence of carbon, hydrogen and oxygen was already confirmed, however, there was no detection of nitrogen or its compounds. Molecular nitrogen is difficult to detect directly. This study concentrates on possible photochemical products of N2 such as HCN, NH3 and HC3N. We set approximate limits on the amount of nitrogen bearing species by varying atmospheric parameters, such as the Eddy Diffusion coefficient and the amount of N2 present from 10 ppm to 10%. If the bulk nitrogen-containing gas in the atmosphere is N2, photochemistry produces only trace amounts of the aforementioned species. However, if ammonia is the main source of nitrogen, then the quantities of NH3, CH5N and HCN approach detectable range. HC3N and NO are bad tracers of the nitrogen source in the atmosphere, because they are produced in similar amounts in all tested scenarios. Assuming equilibrium chemistry at the surface of K2-18b results in underprediction of CO2 abundance. This result combined with the non-detection of ammonia by JWST suggests the planet is not a typical sub-Neptune, but could be indeed a hycean world or magma ocean planet. We also found that C2H6 is produced in significant amounts - if it is detected in the future, it could serve as a proxy for DMS presence.
Keywords: 5109 Space Sciences